Odpowiedź:
1.
a) 2(x-4)-2x = 2x-8-2x = -8
b) -3(t+2a)-4t = -3t-6a-4t = -7t - 6a
c) (3a-6bc):3 = a - 2bc
d) -5(2t-8)+4(3t+5) = -10t+40+12t+20 = 2t + 60
e) (8x-2):2 + (-6x+7-y) = 4x-1-6x+7-y = -2x - y + 6
f) -7x-(2x-3y)+4(-2x-5y) = -7x-2x+3y-8x-20y = -17x - 17y
g) (15g-10):5 - (14g+21):7 = 3g-2 - 2g+3 = g + 1
2.
a) A+B+C = (x²-3x+1)+(-4x²-3)+(6x+12) = x²-3x+1-4x²-3+6x+12 = -3x² + 3x + 10
b) B-D-A = (-4x²-3)-(-3x²-5x+2)-(x²-3x+1) = -4x²-3+3x²+5x-2-x²+3x-1 = -2x² + 8x - 6
c) A-C+D = (x²-3x+1)-(6x+12)+(-3x²-5x+2) = x²-3x+1-6x-12-3x²-5x+2 = -2x² - 14x - 9
d) D-A-B = (-3x²-5x+2)-(x²-3x+1)-(-4x²-3) = -3x²-5x+2-x²+3x-1+4x²+3 = -2x + 4
e) C+B-A = (6x+12)+(-4x²-3)-(x²-3x+1) = 6x+12-4x²-3-x²+3x-1 = -5x² + 9x + 8